Pengembangan Modul Pembelajaran Pendidikan Akhlak untuk Meningkatkan Sikap Toleransi Siswa di SMAS An-Nizam Islamic Boarding School - Muhammad Rizqy Fadhlan; Zailani Zailani (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
Moral education is an essential aspect of shaping students’ character, particularly in fostering tolerance within diverse school environments. However, existing teaching materials tend to be theoretical and provide limited opportunities for students to internalize moral values in real life. This study aims to develop a moral education learning module to enhance students’ tolerance at SMAS An-Nizam Islamic Boarding School. The research employed a Research and Development (R&D) method using a simplified Borg & Gall model, which included needs analysis, design, expert validation, limited trials, and revision. The results show that the developed module is based on a contextual-humanistic approach and integrates methods such as discussion, case studies, reflection, and creative projects. Limited trials indicated an improvement in students’ tolerance, reflected in their ability to collaborate, respect differing opinions, and demonstrate commendable moral behavior in social interactions. The findings imply that the developed moral education module can serve as an alternative teaching material to foster tolerance among students in Islamic boarding schools.